2016
DOI: 10.1590/1413-70542016402025915
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and light intensity interaction on Cercospora coffeicola sporulation and conidia germination

Abstract: Difficulty in obtaining abundant sporulation in culture of many species of Cercospora may be the limiting factor for studies of biology, systematics, and inoculation of the genus. Therefore, it is necessary to understand the nutritional and environmental requirements that influence mycelial growth, sporulation and germination. As it is difficult to obtain conidia of Cercospora coffeicola in vitro, different temperatures (17, 22, 27, and 32 °C) and light intensities (80, 160, 240, and 320 μmol m -2 s -1 ) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…The present study revealed the differences in temperature optima for mycelial growth and asexual fructification of the fungi. The fungal strain had optimal growth at 25⁰C and poor growth at 35⁰C and 4⁰C [35,36]. A research of earlier literature revealed that C. abelmoschi grew well at 25°C in artificial culture while sporulation occurred in the 30°C [18,37].…”
Section: Discussionmentioning
confidence: 99%
“…The present study revealed the differences in temperature optima for mycelial growth and asexual fructification of the fungi. The fungal strain had optimal growth at 25⁰C and poor growth at 35⁰C and 4⁰C [35,36]. A research of earlier literature revealed that C. abelmoschi grew well at 25°C in artificial culture while sporulation occurred in the 30°C [18,37].…”
Section: Discussionmentioning
confidence: 99%
“…Shape and length of conidia: After five days of incubation, a conidial suspension of each isolate was made, and a sample was viewed in a haemocytometer. To determine the size, shape, colour and presence of septa (Silva et al, 2016), fifty conidia from each of the monosporic isolates were evaluated. The length and width of the conidia were measured with an Axiocam 503 colour camera (Carl Zeiss) coupled to an AxioLab.…”
Section: Morphological Characterizationmentioning
confidence: 99%
“…For each isolate obtained, three mycelial discs of the fungus were placed in autoclaved tubes containing 6 mL of distilled water and 4 mL of V8 tomato juice. For sporulation induction, the tubes were shaken at 200 rpm for 5 days (Silva et al, 2016), after which the contents were poured into Petri dishes containing agar-water medium that remained open in a laminar flow cabinet for 3 days or until the culture medium was dehydrated, with continuous light and room temperature at 25°C. Subsequently, 10 mL of sterile distilled water was aliquoted onto the dehydrated culture medium to obtain a conidial suspension.…”
Section: Introductionmentioning
confidence: 99%
“…Growth, sporulation, and germination of fungi are in uenced by environmental variables (SILVA et al, 2016), mainly agrometeorological elements such as air temperature, relative humidity, and leaf wetness duration since changes in the microclimate favor the increased incidence of diseases (PAIVA et al, 2013). Leaf wetness duration is de ned as the time of accumulation of water on the plant tissue surface (SHIN, PARK, KIM, 2021) and is directly related to the rate of infection and pathogen development (JIAN et al, 2020).…”
Section: Introductionmentioning
confidence: 99%